2010
DOI: 10.1186/1749-8090-5-100
|View full text |Cite
|
Sign up to set email alerts
|

An alternate solution for the treatment of ascending aortic aneurysms: the wrapping technique

Abstract: BackgroundThe aortic Dacron wrapping technique is a surgical technique used under certain circumstances in cases of ascending aorta dilatation. Herein, we are presenting our experience on the method performed on multimorbid patients who denied major aortic surgery.MethodsWe included in our series 7 patients (5 male-2 female) with mild to moderate ascending aortic dilatation, who were operated with the wrapping technique. One patient was submitted to biological aortic valve replacement during the same procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Seventeen papers were selected for analysis of wrapping with and without concomitant aortoplasty through database and hand searching [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen papers were selected for analysis of wrapping with and without concomitant aortoplasty through database and hand searching [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This may be the reason for fewer complications (redilatation, wall degeneration, dissection) in patients with wrapping without reduction aortoplasty. An aortoplasty with wrapping probably does not offer additional advantages over an isolated wrapping in moderately dilated aorta 9,18,[21][22][23] Wrapping R Aortoplasty (Wall Resection) 4,8,10,[13][14][15][16][17][18][19][20] Wrapping R Aortoplasty (Wall Plication) 3,11,12,17,24 (40 to 55 mm). However, this combined technique may be useful when dealing with the aorta of a greater diameter as it could prevent aortic wall deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients with connective‐tissue diseases, including Marfan's syndrome, or acute or chronic dissection should be excluded . Wrapping of the ascending aorta is ideal for patients who have multiple co‐morbidities and for whom a prolonged operative time would significantly increase their mortality risk …”
Section: Discussionmentioning
confidence: 99%
“…In general, surgery with concomitant cardiovascular procedures especially involving the aortic valv 4 borderline dilated distal ascending aortae with a felt or prosthetic graft to prevent dilation over the long term. Some reports have indicated that wrapping effectively preserves dilated ascending aortae [2][3][4]. However, we recently experienced a need to re-operate on a replaced distal ascending aorta of a male patient that had become dilated despite being wrapped with a prosthetic graft (Figure 4).…”
Section: Discussionmentioning
confidence: 99%